Rejuvenation of Old People with Stem Technology - Akash1 , Geetha R V2 , Jayalakshmi Somasundaram3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Rejuvenation is a process of reverse practice of the process of aging. This can be done by stem cellsstimulated by the induced growth factors in an active cell division. Senescent cells can be removed by theimmune system, this is destroyed by gene therapy. There are some preformulated drugs available whichare the precursor thought of this article.In the last few decades, there has been a substantial increase in thepopulation of people over 60 years of age. Most of them maintain a good general health and physical activityand fitness. For these individuals there is a good number of dermatologic procedures, medications, andcosmetics that can be prescribed to improve the aspect of skin aging, providing an improvement in their selfesteem and quality of life as a result of their better look. The aim of the research is to study the rejuvenationof old people with stem cell technology